2019
DOI: 10.3389/fpsyg.2019.00904
|View full text |Cite
|
Sign up to set email alerts
|

Non-overlapping and Inverse Associations Between the Sexes in Structural Brain-Trait Associations

Abstract: Personality reflects the set of psychological traits and mechanisms characteristic for an individual. The brain-trait association between personality and gray matter volume (GMv) has been well studied. However, a recent study has shown that brain structure-personality relationships are highly dependent on sex. In addition, the present study investigates the role of sex on the association between temperaments and regional GMv. Sixty-six participants (33 male) completed the Temperament and Character Inventory (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 59 publications
(79 reference statements)
1
15
0
Order By: Relevance
“…So, the difference in personality between genders has a sex-specific neural basis. In our study, what we found is consistent with Stam et al (2019): the difference in implicit gender stereotypic attitudes between male and female have a sex-specific association with the target region, the mPFC. We demonstrated the causal relationship between the mPFC and gender stereotypes by modulating the activity of the mPFC.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…So, the difference in personality between genders has a sex-specific neural basis. In our study, what we found is consistent with Stam et al (2019): the difference in implicit gender stereotypic attitudes between male and female have a sex-specific association with the target region, the mPFC. We demonstrated the causal relationship between the mPFC and gender stereotypes by modulating the activity of the mPFC.…”
Section: Discussionsupporting
confidence: 93%
“…In terms of the neural substrates of gender difference, Stam et al (2019) demonstrated that brain structure-personality associations are dependent on sex. Specifically, in some brain regions, there were inverse associations between temperament and regional gray matter volume (GMv) in males and females, and the brain regions related to gender and temperament were non-overlapping.…”
Section: Discussionmentioning
confidence: 99%
“…Irrespective of observer's gender, happy female but angry male walking with subtle emotional expression is most often mistaken for neutral locomotion (42). The neurobiological mechanisms underlying such gender differences remain to be clarified, including potential differences in grey matter volume (43) and effective and anatomical white-matter connectivity (6,44,45).…”
Section: Discussionmentioning
confidence: 99%
“…Women tend toward better social and linguistic skills, while men tend toward higher physical abilities combined with technical, spatial, and navigating (Tay et al, 2019). Inborn essentially driven behavioral differences in the brain are thus limited to factors surrounding reproduction (Stam et al, 2019;Joel & McCarthy, 2017;Arnold et al, 2004).…”
Section: Canalized Reproductive Behaviormentioning
confidence: 99%
“…Differences between the sexes for emotional processing are well-acknowledged (Kreukels & Guillamon, 2016). Behaviours related to reproduction are recognizable in differences in the levels of responses such as sociability, attachment, sentimentality (Stam et al, 2019), aggression (Zell et al, 2015), in defend or befriend (Hoekzema et al, 2017;Sokolowski & Corbin, 2012;McCarthy et al, 2012;Pearson et al, 2009;Zietsch et al, 2008), instinct (Sweatt et al, 2013), and significantly empathy (Swain et al, 2007).…”
Section: Care Of Offspringmentioning
confidence: 99%